A finite-strain phase-field approach to ductile failure of frictional materials. (1st November 2019) - Kienle, Daniel; Aldakheel, Fadi; Keip, Marc-André
Abstract: This work presents a modeling framework for the ductile failure of frictional materials undergoing large deformations with a focus on soil mechanics. Crack formation and propagation in soil can be modeled in a convenient way by the recently developed continuum phase-field approach to fracture. Within this approach sharp crack discontinuities are regularized. It allows the use of standard discretization methods for crack discontinuities and is able to account for complex crack paths. In the present contribution, we develop a computational modeling framework for the phase-field approach to ductile fracture in frictional materials. It combines a non-associative Drucker–Prager-type elastic-plastic constitutive model with an evolution equation for the crack phase field in terms of an elastic-plastic energy density. An important aspect is the development of an isotropic hardening mechanism that accounts for both friction and cohesion hardening . In order to guarantee a locking- and hourglass-free response, a modified enhanced element formulation, namely the consistent-gradient formulation, is employed as a key feature of the finite-element implementation. The performance of the formulation is demonstrated by means of representative numerical examples that describe soil crack formation rooted in elastic-plastic fracture mechanics.